2001
DOI: 10.1002/ijc.1594
|View full text |Cite
|
Sign up to set email alerts
|

Biodistribution of hypericin in orthotopic transitional cell carcinoma bladder tumors: Implication for whole bladder wall photodynamic therapy

Abstract: In a recent clinical study, we reported a selective uptake of hypericin in superficial bladder tumors. The results suggested that hypericin, a potent photosensitizer, could be used not only for diagnosis but also for photodynamic therapy (PDT) of superficial bladder tumors. In the present study, we investigated the biodistribution of hypericin in an orthotopic rat bladder tumor model by assessing the extent of hypericin penetration and the kinetics of accumulation into rat bladder tumors and normal bladder wal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 42 publications
(46 reference statements)
3
53
0
Order By: Relevance
“…For Hyp, several studies report a tumor-cell specific accumulation; for example, Kamuhabwa et al found a 12:1 ratio of fluorescence for specific tumor accumulation in superficial bladder tumors after 4 hr of instillation with 30 µM Hyp implicating the possibility of whole bladder wall PDT for superficial bladder tumors [89]. A tumor-specific retention was demonstrated by Xie et al in a human prostate model system.…”
Section: Tumor-cell Specific Accumulation Of Hypmentioning
confidence: 95%
“…For Hyp, several studies report a tumor-cell specific accumulation; for example, Kamuhabwa et al found a 12:1 ratio of fluorescence for specific tumor accumulation in superficial bladder tumors after 4 hr of instillation with 30 µM Hyp implicating the possibility of whole bladder wall PDT for superficial bladder tumors [89]. A tumor-specific retention was demonstrated by Xie et al in a human prostate model system.…”
Section: Tumor-cell Specific Accumulation Of Hypmentioning
confidence: 95%
“…In vitro and in vivo photodynamic effects inducing apoptosis and/or necrosis of various malignant cells, such as human glioblastoma cell lines (22), human HL-60 promyelocytic leukaemia cells and CD4 + T-cells (23), rat bladder transitional cell carcinoma (24), human colon carcinoma and hepatoma cell lines (25) as well as human pancreatic cancer (26), were demonstrated. In vitro hypericin accumulates in glioma cells significantly higher than in neurones (27,28).…”
Section: Introductionmentioning
confidence: 99%
“…10,11 . Following bladder instillation, hypericin remains limited to malignant or benign urothelium, but the ratio tumor to normal urothelium seems rather low in animal studies (0.6 -1.5, depending of the instillation conditions), by opposition to clinical observations in human 12,13 . According to hypericin sub-cellular localization in mitochondria and lysosomes, apoptosis as cell death mechanism may be involved in hypericin induced PDT 14 .…”
Section: Hypericinmentioning
confidence: 86%